me Edukasi pemanfaatan air hujan sebagai sumber air bersih menggunakan alat filtrasi sederhana: edukasi air brsih - Suma, Aldi; Lokden, Ester Elisabet; Numberi, Isomi Salmon Frendy; Yekwam, Marice Agusta; Irianti, Yunita (LRI Universitas Muhammadiyah Sorong, 2025)
Rainwater is a source of clean water that can be used to meet human needs such as drinking, bathing, washing, and other basic needs. Rainwater is often ignored and disposed of as runoff. In fact, rainwater has great potential if used as a source of clean water. In some areas, the supply of groundwater and PDAM is not enough to meet the needs of each household. The research was conducted by making a rainwater cross-section tool by providing a water tower that will enter a simple water filtration tool. Decaffeination The research resulted in a simple rainwater collection and filtration system using materials such as silica sand, zeolite, activated carbon, and sponges. The rainwater collected in the tower is then flowed into the filtration tool. As a result, the water that was previously cloudy became clearer and odorless, indicating that the filtration process was going well. Utilization of rainwater as a source of clean water with a collection system, Water collection depends on the planning location. The greater the rainfall, the more water will be collected. The materials / tools used are gutters, collection towers. Good water quality standards are stated in the Republic of Indonesia Government Regulation Number 82 of 2001 concerning Water Quality Management and Water Pollution Control.